Editorial note: Welcome to the year 2025 and Volume 28 - Time to detect kidney disease and protect our kidneys - Assounga, Alain G (African Journal of Nephrology, 2025)
On behalf of the African Journal of Nephrology (AJN) editorial board, I thank all the contributors and readers and wish everyone a very productive 2025. In July 2024, AJN reached a significant milestone by achieving accreditation with CAMES (Conseil Africain et Malgache pour I’Enseignement Supérieur). AJN publications are now accepted for the evaluation of academics from Frenchspeaking African countries. The CAMES accreditation will, therefore, encourage the submission of articles in French. We look forward to receiving, evaluating, and publishing more French manuscripts. Volume 27 included many highlights. An editorial by Luyckx et al. focused on the need to translate knowledge into action to improve kidney care. Several original articles reported on research on kidney diseases in various parts of Africa. I wish to mention the publication on living kidney donors, a report on CKD screening on World Kidney Day in Nigeria and a publication on acute kidney injury in Zambian children. Finally, a report on the South African Renal Registry summarised the latest data on the treatment of kidney failure in South Africa. Last year, we proposed that society and the nephrology community should support individuals in taking primary responsibility for their kidneys. Education programmes which ensure the provision of appropriate information would yield better outcomes [1]. Taking a leaf from HIV management, large-scale educational activities could empower patients and improve treatment adherence. HIV is the third-leading cause of CKD in the province of KwaZulu-Natal, South Africa; hence, strategies to detect CKD and delay CKD progression need to be incorporated in HIV clinics [2]. I am impressed to note that patients living with HIV know their viral load and CD4 counts. They are, therefore, empowered to take their treatment seriously to maintain or improve the control of HIV and immune function. Similarly, I invite everyone to check and take note of their eGFR and proteinuria status annually, as these are key markers of kidney health. Half of the work is done by knowing the kidney’s health status. The nephrology community should contribute by supporting individuals in managing and improving the above parameters. On March 13, 2025, the world will celebrate World Kidney Day. This year, the theme is “Are your kidneys ok? Detect early, protect kidney health”. Therefore, let us move to detect kidney disease early and protect our kidneys.